Emergency Blended Teaching and Learning Amidst the Covid-19 Pandemic - Risma Fitria Uky Yandini; Hanna Hanna; Alberth Alberth (Halu Oleo University, 2022)
This paper is rooted in the self-narration of 23 vocational high school community members in East Kolaka who were directly affected by the implementation of emergency blended teaching and learning due to the outbreak of the Coronavirus. This paper attempted to answer the question: “What do the school community members perceive as the advantages and drawbacks of emergency blended teaching and learning in language learning?” Applying phenomenology approach in qualitative research design, the result shows the advantages are categorized into several aspects: individualization, collaboration, information resources, reduce dependence on online games and social media also and emergency blended teaching and learning also had a potential to be used during praktek kerja industri (industry working practice). However, school community members also faced a few difficulties when implementing emergency blended teaching and learning, particularly in language teaching and learning. The drawbacks are categorized into several catagories: culture, instructional design, learning outcomes, psychology effect, device and internet accessibility concerns. Despite highly regarded as a viable answer to continuing academic activities within the limits of face-to-face contact due to the outbreak of Covid-19 Pandemic, in East Kolaka, emergency blended teaching and learning carries a stigma of being lower quality than face-to-face learning.